Wahala : a novel - May, Nikki (Custom House, 2022)
"An incisive and exhilarating debut novel following three Anglo-Nigerian best friends and the lethally glamorous fourth woman who infiltrates their group-the most unforgettable girls since Carrie, Miranda, Charlotte, and Samantha"--